Carbon fiber bundle and carbon fiber-reinforced composite material using same
By optimizing the single fiber diameter, wire harness strength and interface adhesion of the carbon fiber bundle, the shortcomings in the tensile strength of the carbon fiber composite material and the pressure resistance of the pressure vessel in the prior art are solved, and efficient strength presentation and pressure resistance improvement are achieved.
Patent Information
- Application Number
- CN202380058524.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-29
- Filing Date
- 2023-10-10
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art has limitations in improving the tensile strength and strength utilization of carbon fiber composites, and when designing pressure vessels, there is a deviation between the resin impregnated wire harness strength and the 0° tensile strength of the actual carbon fiber composite.
By designing optimized carbon fiber bundles, using specific resin formulations and manufacturing processes, the single fiber diameter, wiring harness strength and strength utilization of carbon fiber bundles are improved, and the interface adhesion between carbon fiber and resin is optimized to achieve efficient tensile strength presentation.
The efficient tensile strength of carbon fiber reinforced composite materials and the pressure resistance of pressure vessels have been improved, and the shortcomings in strength utilization and pressure resistance in the prior art have been solved.
Smart Images

Figure BDA0005264499410000221 
Figure BDA0005264499410000222 
Figure BDA0005264499410000261
Abstract
Description
Technical Field
[0001] The present invention relates to a carbon fiber bundle suitable for use in aircraft parts, automobile parts, and ship parts, as well as in sports applications such as golf clubs and fishing rods, and other general industrial applications. Background Art
[0002] Polyacrylonitrile (hereinafter, sometimes referred to as "PAN") carbon fibers have higher specific strength and specific elastic modulus than other fibers. Therefore, as reinforcing fibers for composite materials, in addition to conventional sports applications and aviation and aerospace applications, they are also being widely developed in general industrial applications such as automobiles, civil engineering and construction, pressure vessels, and wind turbine blades, and there is a strong demand for further high performance.
[0003] One of the ways to improve the tensile strength of carbon fiber reinforced composite materials (hereinafter sometimes referred to as "carbon fiber composite materials") is to improve the degree to which the mechanical properties (i.e., strength utilization rate) of carbon fiber can be efficiently exhibited when making reinforcing fibers for composite materials, in addition to simply improving the strand strength of the carbon fiber itself.
[0004] So far, several schemes have been proposed for the purpose of improving strength utilization. Patent Documents 1 and 2 propose the following technology: the surface layer of the carbon fiber bundle obtained from the precursor fiber bundle whose density is improved by dry-wet spinning is electrolytically oxidized in an electrolyte aqueous solution containing nitrate ions as an essential component. In addition, Patent Document 3 proposes the following technology: improving the strength of the wire bundle and the limit tension of broken wires, thereby preventing fuzzing and broken wires during molding by filament winding, and making the tensile strength in the obtained cylinder better. In Patent Document 4, by adjusting the rigid modulus of the rubber-like flat part above the glass transition point, the impact resistance, tensile strength, and compressive strength of the carbon fiber composite material are improved. In Patent Document 5, by adjusting the rigid modulus of the rubber-like flat part above the glass transition point, the interlaminar toughness and compressive strength of the carbon fiber composite material in a high temperature environment are improved. In Patent Document 6, by adjusting the compressive yield stress of the resin cured product, the compressive strength of the carbon fiber composite material is improved. Patent documents 7 to 10 propose to improve the moldability of carbon fiber composite materials by preventing fiber breakage, improving the fiber opening property of carbon fiber bundles when molding carbon fiber composite materials, and improving the strength presentation by eliminating the unimpregnated and excess parts of the resin. Patent document 7 proposes the following technology: by blowing gas to remove the sizing agent on the outer layer of the carbon fiber bundle after the sizing agent is attached to the inner layer of the carbon fiber bundle, a technology that simultaneously achieves friction resistance, fiber breakage resistance, and resin impregnation. Patent document 8 proposes the following technology: by interweaving the carbon fiber precursor fiber bundle, it is not easy to produce fiber breakage when opening the fiber to make a composite material, thereby improving the moldability when making a composite material. Patent document 9 proposes the following technology: the fiber diameter of each single fiber constituting the carbon fiber bundle is reduced, and a groove of a specific depth in the fiber axial direction is formed on the surface of the single fiber, thereby improving the impregnation of the resin. In addition, Patent document 10 proposes the following technology: by making the shape of the carbon fiber bundle flat, the fiber opening property during molding is improved, so as to make a homogeneous molded body. In Patent Document 11, the crystal structure in the carbon fiber is controlled to a preferred state according to the firing conditions of the flame retardant carbonization process, so that the 0° tensile strength of the carbon fiber composite material is easily exhibited. In addition, in Patent Document 12, as a technology for suppressing the reduction of mechanical properties from processing the carbon fiber bundle into a prepreg form to processing into a final molded product, a technology for hydrolyzing the remaining epoxy group contained in the sizing agent before or after the sizing agent is applied to the carbon fiber bundle, or before and after the sizing agent is applied.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Publication No. 5-4463
[0008] Patent Document 2: Japanese Patent Publication No. 4-9227
[0009] Patent Document 3: Japanese Patent No. 3047731
[0010] Patent Document 4: Japanese Patent Application Publication No. 2001-323046
[0011] Patent Document 5: International Publication No. 2016 / 67736
[0012] Patent Document 6: Japanese Patent Application Publication No. 2003-277471
[0013] Patent Document 7: Japanese Patent No. 6543309
[0014] Patent Document 8: Japanese Patent Application Publication No. 2020-059937
[0015] Patent Document 9: Japanese Patent No. 4533518
[0016] Patent Document 10: Japanese Patent Application Publication No. 2002-294568
[0017] Patent Document 11: Japanese Patent No. 7239401
[0018] Patent Document 12: Japanese Patent No. 6051987 Summary of the invention
[0019] Problems to be solved by the invention
[0020] However, in the technologies of Patent Documents 1 and 2, although the improvement of the bundle strength was confirmed in both resins before and after the nitric acid treatment, since the single fiber fine carbon fiber needs to be treated with nitric acid as a post-treatment, dried, and inactivated at 700°C in a nitrogen atmosphere for several minutes, there are also problems in terms of grade reduction caused by the generation of fluff, productivity and cost caused by the accompanying post-treatment. In the technology of Patent Document 3, in order to measure the tensile strength of the cylinder formed by filament winding, the same resin as the bundle evaluation is used. Therefore, although it is possible to evaluate whether there is a decrease in strength caused by filament damage in the molding process of filament winding, the improvement of the strength utilization rate caused by the difference in resin is not sufficient. In Patent Documents 4 to 6, although the mechanical properties of epoxy resin cured products are designed to maximize the mechanical properties of existing carbon fibers, they are limited to resins of specific compositions and are therefore not technologies that can be applied to carbon fiber composite materials for a wide range of uses. The technologies of Patent Documents 7 to 10 are only technologies for improving the moldability of carbon fiber bundles. When good moldability has been established, there is no hope of improving the mechanical properties. In Patent Documents 8 and 9, since the diameter of the single fibers constituting the carbon fiber bundle is thin, the productivity of the carbon fiber bundle itself and the reduction in quality due to the generation of fluff during processing become issues. In Patent Document 10, as a matrix resin when making a carbon fiber composite material, a main agent and curing agent described in the resin impregnation bundle strength test method of JIS R7608 (2007) is used, which is a technology for suppressing the reduction in strength when the test piece is shaped into a cylindrical shape. In addition, in the technology of Patent Document 11, it is emphasized that the 0° tensile strength of the carbon fiber composite material is high relative to the resin impregnation bundle strength of the carbon fiber bundle, but as an absolute value of strength, sufficient strength is not obtained. The technology of Patent Document 12 is a technology for suppressing the reduction in strength that occurs from processing into a prepreg blank form to processing into a final molded product, and is not a technology for improving strength.
[0021] In addition, as an evaluation method for the strength of the resin-impregnated strand, the evaluation method using the resin composition and method based on JIS R7608 (2007) is excellent in that the preparation of the test piece is simple and stable test results can be obtained, but it has fewer functional groups than practical resins used as carbon fiber composite materials, and the adhesion to the carbon fiber bundle is often low. Therefore, there is sometimes a deviation between the strength of the resin-impregnated strand specified in JIS R7608 (2007) and the 0° tensile strength of the carbon fiber composite material using practical resins.
[0022] Since the 0° tensile strength of carbon fiber composite materials is dominant for the pressure resistance of pressure vessels, the deviation between the resin impregnated strand strength specified in JIS R7608 (2007) and the 0° tensile strength of carbon fiber composite materials using practical resins becomes a problem when designing pressure vessels. In particular, in carbon fiber bundles with a single fiber diameter of 6.6 μm or more, which are commonly used as carbon fiber bundles for pressure vessels, a deviation between the strand strength evaluated by JIS R7608 (2007) and the pressure resistance performance in the pressure test of pressure vessels was observed.
[0023] On the other hand, even if the resin composition specified in JIS R7608 (2007) is simply changed to a practical resin, for example, when the original viscosity of the resin is high, when the reactivity of the resin is high and the viscosity is easily increased during the impregnation of the resin, there will be problems such as insufficient impregnation of the carbon fiber bundle with the resin, large deviations in the evaluation results, and inability to perform appropriate evaluation.
[0024] To this end, the present invention has discovered an evaluation method using a resin composition that reflects the strength exhibited when a carbon fiber composite material is made, with the aim of providing a carbon fiber bundle that can efficiently exhibit tensile strength when a carbon fiber composite material is made by optimally designing the method for making the carbon fiber bundle, the interfacial adhesion between the carbon fiber bundle and the resin, or both.
[0025] Means for solving problems
[0026] In order to achieve the above-mentioned object, the present invention includes the following configurations.
[0027] (1) A carbon fiber bundle to which a sizing agent is applied, wherein the strand strength (strand strength A') evaluated based on JIS R7608 (2007) using the following resin formulation A is 5.0 GPa or more and 6.0 GPa or less, and the strand strength (strand strength B') evaluated based on JIS R7608 (2007) using the following resin formulation B is 4.7 GPa or more and 5.5 GPa or less, the ratio of the strand strength B' to the strand strength A' is 85% or more, and the single fiber diameter of the carbon fiber bundle is 6.0 μm or more,
[0028] Resin formula A: "CELLOXIDE (registered trademark)" 2021P / boron trifluoride monoethylamine / acetone = 100 / 3 / 4 (parts by mass), and as curing conditions, normal pressure, temperature 125°C, and time 30 minutes;
[0029] Resin formulation B: "JER (registered trademark)" 828 / dicyandiamide / 3-(3,4-dichlorophenyl)-1,1-dimethylurea = 100 / 6.3 / 2 (parts by mass), and curing conditions were normal pressure, temperature of 130° C., and time of 90 minutes.
[0030] (2) The carbon fiber bundle as described in (1), wherein the product E×d / W of the ratio d / W of the single fiber diameter d to the coil width W just before breakage evaluated by the single fiber coil method and the bundle elastic modulus E is 12.6 GPa or more.
[0031] (3) The carbon fiber bundle according to (1) or (2), wherein the surface area ratio of the single fibers is 1.00 to 1.08.
[0032] (4) A carbon fiber bundle as described in any one of (1) to (3), wherein the bundle strength (bundle strength C') evaluated based on JIS R7608 (2007) using the following resin formulation C is 4.8 GPa or more and 5.5 GPa or less, the ratio of the bundle strength C' to the bundle strength A' is 85% or more, the single fiber diameter of the carbon fiber bundle is 6.6 μm or more, and the interface shear strength is 16 MPa or less,
[0033] Resin Formulation C: Araldite (registered trademark) LY1564 SP CI / Baxxodur (registered trademark) EC331 = 100 / 35 (parts by mass) was used, and the curing conditions were normal pressure, temperature 80°C, time 120 minutes, and then normal pressure, temperature 110°C, time 240 minutes.
[0034] (5) The carbon fiber bundle according to (4), wherein the strand strength C' is 5.0 GPa or more and 5.5 GPa or less.
[0035] (6) The carbon fiber bundle as described in (4) or (5), wherein the sizing agent contains at least one epoxy group-containing component, and when the epoxy value of the sizing agent dissolved by immersing the carbon fiber bundle in N,N-dimethylformamide and performing ultrasonic treatment is X meq. / g, and the adhesion ratio of the sizing agent applied to the carbon fiber bundle is Y mass %, the relationship of the following formula 1 is satisfied:
[0036] 0.10meq. / g≤X×Y≤0.68meq. / g…Formula 1.
[0037] (7) The carbon fiber bundle according to any one of (4) to (6), wherein the drape value is greater than 0 cm and 18 cm or less.
[0038] (8) The carbon fiber bundle according to (7), wherein the drape value is not less than 4 cm and not more than 10 cm.
[0039] (9) A carbon fiber reinforced composite material using the carbon fiber bundle according to any one of (1) to (8).
[0040] (10) A pressure vessel using the carbon fiber bundle according to any one of (1) to (8).
[0041] Effects of the Invention
[0042] By using the carbon fiber bundle of the present invention, the tensile strength of the carbon fiber reinforced composite material can be effectively improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] [ Figure 1 ] Figure 1 It is a figure which shows the preparation method of the sample used for measuring the drape value.
[0044] [ Figure 2 ] Figure 2 It is a figure which shows the measuring method of the drape value.
[0045] [ Figure 3 ] Figure 3 This is a schematic diagram of an apparatus for performing a pressure test on a pressure vessel. DETAILED DESCRIPTION
[0046] For the carbon fiber bundle of the present invention, the bundle strength evaluated according to the tensile test method for resin-impregnated bundles described in JIS R7608 (2007) and using the following resin formula A which is a combination of resins described in JIS R7608 (2007) (hereinafter, the bundle strength in the case of the resin formula A is sometimes referred to as "bundle strength A'") is 5.0 GPa to 6.0 GPa, preferably 5.5 GPa to 6.0 GPa, and more preferably 5.7 GPa to 6.0 GPa.
[0047] Resin formulation A: "CELLOXIDE (registered trademark)" 2021P / boron trifluoride monoethylamine / acetone = 100 / 3 / 4 (parts by mass), and curing conditions were normal pressure, temperature of 125°C, and time of 30 minutes.
[0048] The wire bundle strength A' is an index indicating the difficulty of breaking when a load is applied to the carbon fiber, and is an index indicating the strength of the carbon fiber bundle itself. If the wire bundle strength A' is 5.0 GPa or more, it is easy to improve the strength when it is made into a carbon fiber composite material. The higher the wire bundle strength, the better. However, when the wire bundle strength A' is preferably 5.5 GPa or more, and more preferably 5.7 GPa or more, it is easy to become a carbon fiber composite material that is extremely excellent in practical use. The wire bundle strength A' can be controlled by manufacturing according to the manufacturing method of carbon fiber described later.
[0049] For the carbon fiber bundle of the present invention, the bundle strength evaluated by the tensile test of the resin-impregnated bundle described in JIS R7608 (2007) using the following resin formulation B (hereinafter, the bundle strength in the case of the resin formulation B is sometimes referred to as "bundle strength B'") is 4.7 GPa to 5.5 GPa, preferably 4.9 GPa to 5.5 GPa.
[0050] Resin formulation B: "JER (registered trademark)" 828 / dicyandiamide / 3-(3,4-dichlorophenyl)-1,1-dimethylurea = 100 / 6.3 / 2 (parts by mass), and curing conditions were normal pressure, temperature of 130° C., and time of 90 minutes.
[0051] Resin formula B is a resin used for filament winding (tow impregnation) in a dry process, and has a viscosity suitable for making a harness test piece using the impregnation method described in JIS R7608 (2007). Compared with resin formula A, which is a combination of resins described in JIS R7608 (2007), resin formula B has more functional groups and higher adhesion to carbon fiber bundles, so the bundle strength B' is an index that represents the strength of a carbon fiber bundle when it is made into a carbon fiber composite material in a modeled manner. If the bundle strength B' is 4.7 GPa or more, it is easy to improve the strength when the carbon fiber composite material is actually made. In addition, if the bundle strength B' is 4.9 GPa or more, it is easy to become a carbon fiber composite material with extremely excellent practicality. The bundle strength B' can be controlled by improving the compactness of the carbon fiber precursor fiber bundle according to the manufacturing method of carbon fiber described later, or by adjusting the interface adhesion between the carbon fiber and the resin, or by both.
[0052] The ratio of the bundle strength B' to the bundle strength A' of the carbon fiber bundle of the present invention (bundle strength B' / bundle strength A'. Hereinafter, sometimes referred to as "strength utilization rate α") is 85% or more, preferably 88% or more. The strength utilization rate α is an indicator of the strength presented when a certain carbon fiber bundle is made into a carbon fiber composite material. If the strength utilization rate α is 85% or more, the mechanical properties of the carbon fiber can be efficiently presented when the carbon fiber composite material is made. The closer the strength utilization rate α is to 100%, the more preferred it is, but in most cases, 88% or more is sufficient as a carbon fiber composite material.
[0053] The single fiber diameter of the carbon fiber bundle of the present invention is 6.0 μm or more, preferably 6.6 μm or more, and more preferably 6.8 μm or more. Since the breaking load of each single fiber is determined by the bundle strength and the single fiber cross-sectional area, the single fiber diameter affects the breaking load of each single fiber. In addition, the larger the single fiber diameter, the less fuzzing caused by friction in the process tends to be, thus affecting the grade. If the single fiber diameter is 6.6 μm or more, the grade is easy to become good when the carbon fiber is produced and when the carbon fiber composite material is made. On the other hand, if the single fiber diameter becomes too large, the reaction may occur in the single fiber during the firing process and become uneven, so a single fiber diameter of 6.8 μm or more is sufficient, preferably 8.0 μm or less.
[0054] The carbon fiber bundle of the present invention can achieve improved tensile strength when made into a carbon fiber composite material and improved pressure resistance as a pressure vessel by ensuring that the bundle strength, strength utilization rate α, and single fiber diameter in the case of resin formulation A and resin formulation B all meet the ranges described above.
[0055] The product E×d / W of the ratio d / W of the single fiber diameter (d. The unit is μm. For convenience, it is sometimes referred to as the "single fiber diameter d") of the carbon fiber bundle of the present invention and the coil width just before breaking evaluated by the single fiber coil method (W. The unit is μm. For convenience, it is sometimes referred to as the "coil width W just before breaking evaluated by the single fiber coil method") and the elastic modulus of the wire bundle (E. The unit is GPa) is preferably 12.6 GPa or more. It should be noted that, here, the elastic modulus of the wire bundle (sometimes referred to as the "wire bundle elastic modulus E" for convenience) is obtained using the above-mentioned resin formula A and the method described in the item of the embodiment. There is no particular upper limit for the product E×d / W, and the higher the better, but it is practical to set it below 14 GPa.
[0056] The single fiber coil method is a method for investigating the relationship between the strain imparted to a single fiber by deforming the single fiber into a coil shape and the destructive behavior of the single fiber such as breakage and buckling. When the single fiber is deformed into a coil shape, a compressive strain is imparted to the inner side of the single fiber and a tensile strain is imparted to the outer side of the single fiber. Since compressive buckling occurs before tensile failure, the single fiber coil method has been used as a test method for the compressive strength of a single fiber of a carbon fiber bundle in the past, but by evaluating the breaking strain, it is possible to evaluate the value of the bending strength that can be said to be achieved by the carbon fiber bundle. That is, d / W is a value proportional to the strain, and the product of this value and the elastic modulus E of the bundle can be said to be a value equivalent to the strength. Sometimes, only increasing the bundle strength of the carbon fiber bundle cannot improve the tensile strength of the composite material, but by increasing this E×d / W, the tensile strength of the composite material can be effectively improved. The upper limit of this E×d / W is not particularly limited, and it is sufficient to set 19.0GPa as the upper limit of E×d / W. It should be noted that this parameter can be controlled by improving the density of the carbon fiber precursor fiber bundle according to the method for manufacturing a carbon fiber bundle of the present invention described later.
[0057] For the carbon fiber bundle containing a sizing agent of the present invention, the bundle strength evaluated by the tensile test of the resin-impregnated bundle described in JIS R7608 (2007) using the following resin formula C (hereinafter, the bundle strength of the resin formula C is sometimes referred to as "bundle strength C'") is preferably 4.8 GPa or more and 5.5 GPa or less, more preferably the lower limit is 5.0 GPa or more, and further preferably the lower limit is 5.2 GPa or more.
[0058] Resin Formulation C: Araldite (registered trademark) LY1564 SP CI / Baxxodur (registered trademark) EC331 = 100 / 35 (parts by mass) was used, and the curing conditions were normal pressure, temperature 80°C, time 120 minutes, and then normal pressure, temperature 110°C, time 240 minutes.
[0059] Resin formula C is a practical resin for filament winding applications in a wet process, and has a viscosity suitable for preparing a wire harness test piece using the impregnation method described in JIS R7608 (2007). In addition, compared with resin formula A, which is a combination of resins described in JIS R7608 (2007), resin formula C has more functional groups and higher adhesion to the carbon fiber bundle. Therefore, it was found that the wire harness strength C' can be used as an indicator to model the strength when a certain carbon fiber bundle is made into a carbon fiber composite material.
[0060] If the strand strength C' is 4.8 GPa or more, it is easy to improve the strength of the carbon fiber composite material when it is actually made. In addition, if the strand strength C' is 5.0 GPa or more, it is easy to become a carbon fiber composite material that is extremely excellent in practical use, and 5.5 GPa is sufficient in most cases.
[0061] The strand strength C′ can be controlled by increasing the density of the carbon fiber precursor fiber bundle according to the carbon fiber production method described later, or by adjusting the interface adhesion between the carbon fiber and the resin, or by both.
[0062] The ratio of the bundle strength C' to the bundle strength A' of the carbon fiber bundle of the present invention (bundle strength C' / bundle strength A'. Hereinafter, sometimes referred to as "strength utilization rate β") is preferably 85% or more, and more preferably 88% or more. The strength utilization rate β is an indicator of the strength presented when a certain carbon fiber bundle is made into a carbon fiber composite material. If the strength utilization rate β is 85% or more, the mechanical properties of the carbon fiber can be efficiently presented when the carbon fiber composite material is made. The closer the strength utilization rate β is to 100%, the more preferred it is, but in most cases 88% or more is sufficient as a carbon fiber composite material.
[0063] The interfacial shear strength of the carbon fiber bundle of the present invention is preferably 16 MPa or less, more preferably 12 MPa or more and 16 MPa or less. The interfacial shear strength is an indicator of the adhesion to the resin when the carbon fiber composite material is made. If the adhesion between the carbon fiber and the resin is low, sometimes peeling occurs at the interface between the carbon fiber and the resin, resulting in the fracture of the entire carbon fiber composite material. If it is 12 MPa or more, preferably 14 MPa or more, it can be expected to suppress the peeling at the interface in practice when the carbon fiber composite material is made. If the adhesion between the carbon fiber and the resin is too high, stress concentration is likely to occur at the starting point of the fracture when the carbon fiber composite material is made, resulting in the fracture of the entire carbon fiber reinforced composite material. Therefore, from the perspective of easily improving the bundle strength B', the bundle strength C' or the strength when the carbon fiber reinforced composite material is actually made, it is preferably set to 16 MPa or less.
[0064] In addition, it is preferred that the single fiber diameter of the carbon fiber bundle is greater than 6.6 μm, the bundle strength A' is greater than 5.0 GPa and less than 6.0 GPa, the bundle strength C' is greater than 4.8 GPa and less than 5.5 GPa, the strength utilization rate β is greater than 85% and less than 100%, and the interface shear strength is less than 16 MPa. By making a carbon fiber bundle that satisfies these conditions at the same time, it is advantageous in improving the tensile strength when making a carbon fiber composite material and the pressure resistance as a pressure vessel. It should be noted that these parameters can adopt the aforementioned preferred ranges, and the carbon fiber bundle can be further in the preferred manner described in this specification.
[0065] For the carbon fiber precursor fiber bundle used in the manufacture of the carbon fiber bundle of the present invention, it is preferred that the cross-sectional shape of the monofilament is close to a perfect circle, and the surface concavity is small. Specifically, the roundness of the carbon fiber precursor fiber bundle is preferably in the range of 0.80 to 0.99, and more preferably in the range of 0.90 to 0.99. In addition, the surface area ratio of the carbon fiber precursor fiber bundle is preferably in the range of 1.00 to 1.08, and more preferably in the range of 1.00 to 1.05. If the cross-sectional shape of the monofilament in the precursor fiber bundle deviates from a perfect circle, stress concentration occurs when the stress is loaded as a carbon fiber bundle, and the possibility of breakage becomes higher. From the viewpoint of avoiding this stress concentration, the surface area ratio is preferably less than 1.08, and for the same reason, the roundness is also preferably greater than 0.80. The roundness and surface area ratio can be measured by the method described later and can be controlled by the spinning conditions. For example, a spinning solution maintained at a temperature higher than that of a coagulation bath is temporarily discharged from a spinneret into the air, and introduced into a coagulation bath maintained at a relatively low temperature, the polymer concentration, the solvent concentration of the coagulation bath, and the temperature are set, and the obtained coagulated fibers are stretched, washed with water, treated with an oil agent, steam stretched, etc., thereby manufacturing a carbon fiber precursor fiber bundle having a specific roundness and surface area ratio, and flame retardant and carbonized. The roundness and surface area ratio controlled in the carbon fiber precursor fibers are maintained at approximately the same value even when carbonized, so the carbon fiber bundle of the present invention preferably has a roundness in the range of 0.80 to 0.99, and preferably has a surface area ratio in the range of 1.00 to 1.08.
[0066] The sizing agent used for the carbon fiber bundle of the present invention preferably contains at least one epoxy-containing component. In addition, when the epoxy value of the sizing agent dissolved by immersing the carbon fiber bundle in N,N-dimethylformamide and performing ultrasonic treatment is Xmeq. / g and the sizing agent adhesion ratio given to the carbon fiber bundle is Y mass%, it is preferred to satisfy the relationship of the following formula 1, and it is further more preferred to satisfy the relationship of the following formula 2.
[0067] 0.10meq. / g≤X×Y≤0.68meq. / g…Formula 1
[0068] 0.10meq. / g≤X×Y≤0.40meq. / g…Formula 2.
[0069] The epoxy value is an index indicating the amount of epoxy groups contained in 1 g of the sizing agent. The larger the epoxy value, the more epoxy groups are contained in 1 g of the sizing agent. In addition, the sizing adhesion ratio is expressed as a percentage (mass %) of the total mass of the sizing agent dissolved when the mass of the carbon fiber bundle immersed in N,N-dimethylformamide and subjected to ultrasonic treatment is set to 100 mass %.
[0070] Therefore, X×Y in Formula 1 and Formula 2 is an index indicating the amount of epoxy groups contained per unit mass of the carbon fiber bundle, that is, per 1g. If X×Y is large, the interfacial adhesion between the carbon fiber bundle and the resin is easily improved. If the adhesion between the carbon fiber and the resin is low, peeling occurs at the interface between the carbon fiber and the resin, resulting in the fracture of the entire carbon fiber composite material, which is undesirable. On the other hand, if the adhesion between the carbon fiber and the resin is too high, stress concentration is easily generated at the fracture starting point when the carbon fiber composite material is made, resulting in the fracture of the entire carbon fiber composite material, which is undesirable.
[0071] By controlling X×Y within the range of Formula 1, it is easy to improve the strength of the carbon fiber composite material when it is actually made. In addition, by controlling X×Y within the range of Formula 2, it is easy to obtain a carbon fiber composite material that is extremely excellent in practical use.
[0072] The drape value of the carbon fiber bundle of the present invention is preferably greater than 0 cm and less than 18 cm, more preferably greater than 4 cm and less than 16 cm, and further preferably greater than 4 cm and less than 10 cm. The drape value is an indicator of the hardness of the carbon fiber bundle. The larger the drape value, the harder the carbon fiber bundle exhibits.
[0073] When the drape value is less than 4 cm, the fiber bundle is soft, so when manufacturing a composite material, the yarn guide such as a combing machine used to doubly thread the yarns pulled out from the winding drum is prone to bending and twisting. If bending and twisting occur, it becomes difficult to open the fibers in this part, and uneven fiber opening occurs, which is not desirable. In addition, when the drape value is greater than 18 cm, the fiber bundle becomes hard, so when it is deformed by contact with a yarn guide such as a combing machine, it is sometimes easy to produce fluff. If the drape value is more than 4 cm and less than 10 cm, the uneven fiber opening and the generation of fluff when contacting the yarn guide can be suppressed, so it is preferred.
[0074] The number of filaments of the carbon fiber bundle of the present invention is preferably 12,000 or more, more preferably 24,000 or more. When using filament winding to manufacture composite materials, productivity depends on the yarn speed and the number of filaments, so the composite material can be efficiently manufactured due to the large number of filaments. If the number of filaments is 12,000 or more, it can meet the viewpoint of productivity. The upper limit of the number of filaments is not particularly limited. The more filaments there are, the easier it is to produce a deviation in weight per unit area caused by uneven stretching inside and outside the filament bundle in the stretching process. Therefore, the number of filaments is preferably 36,000 or less.
[0075] Next, a method for producing a suitable carbon fiber bundle for obtaining the carbon fiber bundle of the present invention will be described.
[0076] The carbon fiber precursor fiber bundle of the present invention can be obtained by spinning a spinning solution of a polyacrylonitrile copolymer. As a polyacrylonitrile copolymer, not only a homopolymer obtained from acrylonitrile alone, but also other monomers can be used in addition to acrylonitrile as a main component. Specifically, the polyacrylonitrile copolymer preferably contains 90 to 100% by mass of acrylonitrile and less than 10% by mass of a copolymerizable monomer.
[0077] Examples of the monomer copolymerizable with acrylonitrile include acrylic acid, methacrylic acid, itaconic acid and alkali metal salts, ammonium salts and lower alkyl esters thereof, acrylamide and its derivatives, allylsulfonic acid, methallylsulfonic acid and salts or alkyl esters thereof.
[0078] The aforementioned polyacrylonitrile copolymer is dissolved in a solvent such as dimethyl sulfoxide, dimethylformamide, dimethylacetamide, nitric acid, zinc chloride aqueous solution, sodium thiocyanate aqueous solution, etc., which can dissolve the polyacrylonitrile copolymer, to prepare a spinning solution. When solution polymerization is used in the production of the polyacrylonitrile copolymer, if the solvent used for polymerization and the spinning solvent are set to the same solvent in advance, it is unnecessary to separate the obtained polyacrylonitrile copolymer and dissolve it again in the spinning solvent, which is preferred.
[0079] When manufacturing a carbon fiber precursor fiber bundle, the spinning method can use any of the dry-wet spinning method and the wet spinning method, and preferably the dry-wet spinning method is used, which is beneficial to the knot strength of the obtained carbon fiber bundle. The spinning process includes: a spinning process, which uses the dry-wet spinning method to discharge the spinning solution from the spinning spinneret to the coagulation bath for spinning; a water washing process, which washes the fiber obtained in the spinning process in a water bath; a water bath stretching process, which stretches the fiber obtained in the water washing process in a water bath; and a dry heat treatment process, which performs dry heat treatment on the fiber obtained in the water bath stretching process, and may also include a steam stretching process for steam stretching the fiber obtained in the dry heat treatment process as needed. In addition, as needed, it is preferred to include a filament combination process to be consistent with the number of filaments of the carbon fiber bundle. It should be noted that the order of each process can also be appropriately replaced. The spinning solution is a solution obtained by dissolving the aforementioned polyacrylonitrile polymer in a polyacrylonitrile-soluble solvent such as dimethyl sulfoxide, dimethylformamide and dimethylacetamide.
[0080] The coagulation bath preferably contains a solvent such as dimethyl sulfoxide, dimethylformamide, and dimethylacetamide used as a solvent for the spinning solution, and a coagulation-promoting component. As the coagulation-promoting component, a component that does not dissolve the polyacrylonitrile polymer and is compatible with the solvent used for the spinning solution can be used. Specifically, water is preferably used as the coagulation-promoting component.
[0081] The swelling degree of the coagulated filaments spun from an acrylic polymer solution (hereinafter also referred to as "coagulated filament swelling degree" or simply "swelling degree") is preferably controlled to be less than 120%, and more preferably controlled to be less than 110%. If the swelling degree is less than 3%, the desolventizing in the water washing process takes time, so the lower limit is about 3%. Controlling the swelling degree to 3 to 120% can achieve a balance between the tensile strength and processability of the carbon fiber, so it is more preferred. The coagulated filament swelling degree is an indicator that reflects the density of the carbon fiber precursor fiber bundle. When the carbon fiber precursor fiber bundle is dense, it is easier to improve the density of the obtained carbon fiber bundle. The coagulated filament swelling degree can be reduced by reducing the tension of the coagulation process. For example, by increasing the number of single fibers in the coagulation bath, changing the fixed yarn guide to a free roller, and setting the surface finishing of the fixed yarn guide and the free roller to a pear skin finish, the friction applied to each single yarn can be reduced; or by adjusting the composition and temperature of the coagulation bath to reduce the viscosity of the coagulation bath liquid, changing the yarn path in the coagulation bath, and rectifying it, the fluid resistance of the single yarn from the coagulation bath liquid can be reduced, thereby reducing the tension of the coagulated yarn.
[0082] In the present invention, after the PAN-based polymer solution is introduced into a coagulation bath and coagulated, a water washing step, a stretching step, an oil agent application step, and a drying step are performed to obtain a carbon fiber precursor fiber bundle.
[0083] The water washing step is introduced for the purpose of introducing the coagulated fiber bundle after the air retention step into a water washing bath to further remove the organic solvent from the coagulated fiber bundle. In order to improve the running property of the fiber in the water washing step, the fiber may be stretched 1 to 1.5 times in the water washing step.
[0084] The stretching process can usually be carried out in a single or multiple stretching baths whose temperature is adjusted to 30 to 98°C. The stretching in the bath in the stretching process is called bath stretching, and its ratio is called bath stretch ratio. The bath stretch ratio is preferably set to 2 to 2.8 times. If the total stretch ratio before the oil agent imparting process is greater than 3 times, the density of the surface layer decreases and the oil agent easily penetrates into the fiber. The total stretch ratio before the oil agent imparting process refers to the product of the stretch ratio in the water washing process and the bath stretch ratio.
[0085] The oiling step is a step of applying an oil after the bath stretching step for the purpose of preventing the fibers from adhering to each other. As the oil used in this step, an oil containing silicone as the main component is preferably used. If the oil does not contain silicone, the adhesion between the fibers in the flame retardant step cannot be suppressed, and the strength of the wire bundle is reduced. In addition, the silicone oil is preferably an oil containing modified silicone such as amino-modified silicone with high heat resistance. As other silicone oils, silicone modified by epoxy modification and alkylene oxide modification can be cited.
[0086] The drying process can utilize a known method. In addition, from the viewpoint of improving productivity and crystal orientation, it is preferred to stretch in a heating medium after the drying process. As the heating medium, for example, pressurized steam or superheated steam is suitable from the viewpoint of operational stability and cost.
[0087] It should be noted that a dry heat stretching step or a steam stretching step may be further added after the drying step.
[0088] Next, the method for producing a carbon fiber bundle of the present invention is described. In the method for producing a carbon fiber bundle of the present invention, for example, the carbon fiber precursor fiber bundle produced by the above method is subjected to the following steps to produce a carbon fiber bundle: a flame retardant step of performing flame retardant treatment in an oxidizing atmosphere at a temperature of 200 to 300°C; a pre-carbonization step of performing pre-carbonization treatment in an inert atmosphere at a maximum temperature of 500 to 1,200°C; and then a carbonization step of performing carbonization treatment in an inert atmosphere at a maximum temperature of 1,200 to 2,000°C.
[0089] As the oxidizing atmosphere in the flame retardant treatment, air is preferably used. In the present invention, the pre-carbonization treatment and the carbonization treatment are carried out in an inert atmosphere. Examples of the gas used in the inert atmosphere include nitrogen, argon, and xenon. From the viewpoint of economic efficiency, nitrogen is preferably used.
[0090] In order to modify the surface of the obtained carbon fiber bundle, an electrolytic treatment can be performed. This is because, by electrolytic treatment, the adhesion to the carbon fiber matrix can be optimized in the obtained fiber-reinforced composite material. After the electrolytic treatment, a sizing treatment is performed to give the carbon fiber bundle a bundling property. The sizing agent can be appropriately selected according to the type of resin used. The sizing agent has good compatibility with the matrix resin, but in order to simultaneously achieve the suppression of interface peeling between the carbon fiber and the resin when the carbon fiber composite material is made and the relaxation of stress concentration, and present good mechanical properties, it is important to control the adhesion.
[0091] For this purpose, for example, it is preferred to optimize the electrolytic treatment conditions such as the type and concentration of the electrolyte and the adhesion ratio of the sizing agent to control the amount of functional groups contained in the sizing agent. When the sizing agent contains epoxy groups, it is preferred to adjust the amount of epoxy groups by hydrolyzing the epoxy groups in advance or after the sizing agent is applied to the carbon fiber bundle.
[0092] The production process of the carbon fiber reinforced composite material using the carbon fiber bundle of the present invention can utilize known methods and can be used in many fields such as aviation and aerospace, automobiles, railway vehicles, ships, civil engineering and construction, and sporting goods. In particular, it can be suitable for the production of hollow containers and cylinders such as pressure vessels.
[0093] Example
[0094] The methods for measuring various physical property values used in the present invention are as follows.
[0095] <Coagulation filament tension>
[0096] The coagulated yarn tension is measured at the coagulation bath exit site in the coagulation process. The tension is obtained by clamping the running yarn with a tensiometer and measuring the load, and dividing the load by the process yarn fineness (dtex) at the measurement site.
[0097] <Determination of the degree of swelling of coagulated fibers>
[0098] First, about 10 g of the coagulated fibers are sampled and washed for more than 12 hours. Next, the fibers are dehydrated at 3,000 rpm for 3 minutes using a centrifugal dehydrator (e.g., H-110A manufactured by KOKUSAN Co., Ltd.), and the fiber mass (in g) after dehydration is obtained. The dehydrated sample is then dried in a dryer at 105°C for 2.5 hours, and the fiber mass (in g) after drying is obtained. The coagulated fiber swelling degree is calculated using the following formula. It should be noted that decimal places are rounded off to integers.
[0099] Formula: Coagulated fiber swelling degree (%) = ((fiber mass after dehydration - fiber mass after drying) / fiber mass after drying)) × 100.
[0100] The calculated swelling degree was evaluated in four stages based on the following criteria.
[0101] S: Swelling degree 3% or more and less than 110%
[0102] A: Swelling degree 110% or more and less than 120%
[0103] B: Swelling degree 120% or more and less than 150%
[0104] C: The swelling degree is less than 3% or more than 150%.
[0105] <Total fineness>
[0106] The carbon fiber bundle to be measured was sampled in a length of 10 m, and the mass (in g) measured after drying at 120° C. for 2 hours was divided by 10 to determine the total fineness (in g / m) as the mass per 1 m.
[0107] <Density>
[0108] The measured carbon fiber bundle was dried at 120°C for 2 hours before measurement. For the density measurement, a dry automatic density meter was used, nitrogen was used as the measurement medium, a 10cc sample container was used, and the sample amount was adjusted to 3 to 6cc by volume. Three measurements were performed, and the average value was used. It should be noted that the AccuPyc 1330 dry automatic density meter manufactured by Shimadzu Corporation was used in this measurement.
[0109] <Single fiber diameter>
[0110] The total fineness (g / m2) and density (g / m2) obtained by the above method are 3 ) and the number of filaments in the carbon fiber bundle used for measurement. It should be noted that the unit of the single fiber diameter d is calculated in μm.
[0111] <Carbon fiber bundle strength and bundle elastic modulus>
[0112] The strand strength and strand elastic modulus of the carbon fiber bundle are determined according to the resin impregnation strand strength test method of JIS R7608 (2007) using the respective resin formulations (resin formulation A, resin formulation B, resin formulation C, resin formulation D). It should be noted that the curing conditions are as shown in each resin formulation, and resin formulation B, resin formulation C, and resin formulation D use each formulation instead of resin formulation A. In addition, resin formulation B and resin formulation D are heated to 60°C during impregnation. The strands of 10 carbon fiber bundles were measured, and the average values were taken as the strand strength and strand elastic modulus. The strand elastic modulus is measured within the strain range of 0.1 to 0.6%. It should be noted that the strand elastic modulus (strand elastic modulus E) in the single fiber coil test described later uses the measurement results in resin formulation A.
[0113] <Single fiber coil test>
[0114] A single fiber of about 10 cm in length is placed on a glass slide, 1 to 2 drops of glycerol are dripped in the center, and the two ends of the single fiber are gently twisted in the circumferential direction of the fiber to form a coil in the center of the single fiber, and a cover glass is placed on it. It is set on the stage of a microscope, and video recording is started under the conditions of a total magnification of 100 times and a frame rate of 15 frames / second. While adjusting the stage each time so that the coil does not leave the field of view, the two ends of the fiber that has been coiled are pressed toward the glass slide with fingers and stretched in the opposite direction at a constant speed, thereby applying strain until the single fiber breaks. The frame just before the break is determined by playing it frame by frame, and the width W of the coil just before the break is measured by image analysis. d / W is calculated by dividing the single fiber diameter d by the width W of the coil. 20 measurements are performed, and the average value of d / W is calculated. The average value of d / W is multiplied by the bundle elastic modulus to calculate E×d / W.
[0115] <Measurement of interface shear strength>
[0116] The interface shear strength was measured according to the following procedures (1) to (4).
[0117] (1) Preparation of resin
[0118] 100 parts by mass of bisphenol A epoxy compound "jER (registered trademark)" 828 (manufactured by Mitsubishi Chemical Corporation) and 14.5 parts by mass of m-phenylenediamine (manufactured by Sigma-Aldrich Japan Corporation) were placed in containers. Then, in order to reduce the viscosity of the jER828 and dissolve the m-phenylenediamine, it was heated at 75°C for 15 minutes. Then, the two were fully mixed and vacuum degassed at 80°C for about 15 minutes.
[0119] (2) Fix the carbon fiber monofilament in a special mold
[0120] A single fiber is extracted from the carbon fiber bundle, and both ends are fixed with an adhesive while applying a constant tension to the single fiber along the length direction of the dumbbell-shaped mold. Then, in order to remove the moisture attached to the carbon fiber and the mold, vacuum drying is performed at a temperature of 80°C for more than 30 minutes. The dumbbell-shaped mold is made of silicone rubber, and the shape of the casting part is a mold with a central part width of 5mm, a length of 25mm, a width of 10mm at both ends, and an overall length of 150mm.
[0121] (3) From resin casting to curing
[0122] The resin prepared in the step (1) was poured into the mold after vacuum drying in the step (2), and the temperature was raised to 75°C at a heating rate of 1.5°C / min in an oven and maintained for 2 hours, then raised to 125°C at a heating rate of 1.5°C / min and maintained for 2 hours, and then cooled to 30°C at a cooling rate of 2.5°C / min. Then, the mold was released to obtain a test piece.
[0123] (4) Determination of interface shear strength
[0124] After applying a tensile force in the fiber axis direction (length direction) to the test piece obtained in the above step (3) to generate a strain of 12%, a polarizing microscope is used to measure the number N (pieces) of single fiber breakage sites embedded in the test piece within a range of 22 mm in the center of the length direction of the test piece. Next, the average broken fiber length la is calculated by the formula la (μm) = 22 × 1,000 (μm) / N (pieces). Next, the critical fiber length lc is calculated from the average broken fiber length la by the formula lc (μm) = (4 / 3) × la (μm). Using the bundle strength A' and the single fiber diameter d obtained by the above method, the interface shear strength, which is an indicator of the bonding strength between the carbon fiber and the resin interface, is calculated using the following formula. Five measurements are performed and the arithmetic average is taken as the test result.
[0125] Interface shear strength (MPa) = strand strength A' (MPa) x single fiber diameter d (μm) / (2×1c) (μm).
[0126] <Roundness>
[0127] Cut the carbon fiber precursor fiber bundle or carbon fiber bundle perpendicular to the fiber axis with a razor, and observe the cross-sectional shape of the single fiber using an optical microscope. The measurement magnification is set to 200 to 400 times in a manner that the thinnest single fiber is observed at about 1 mm. The cross-sectional area and circumference of the single fiber are obtained by image analysis of the obtained image, and the diameter (fiber diameter) of the cross section of the single fiber when it is assumed to be a perfect circle is calculated from the cross-sectional area in units of 0.1 μm, and the roundness is calculated using the following formula. The roundness uses the average value of 10 randomly selected single fibers.
[0128] Roundness = 4πS / L 2 (Where S represents the cross-sectional area of the single fiber (in μm 2 ), L represents the circumference of the monofilament (in μm).
[0129] <Surface area ratio>
[0130] Single fibers are extracted from a carbon fiber precursor fiber bundle or a carbon fiber bundle, several extracted single fibers are placed on a sample stand, both ends are fixed with an adhesive (for example, correction fluid for stationery) as a sample, and an atomic force microscope (manufactured by Seiko Instruments, SPI3800N / SPA-400) is used to obtain an image of the three-dimensional surface shape under the following conditions.
[0131] Probe: Silicon cantilever (Seiko Instruments, DF-20)
[0132] Measurement mode: Dynamic force mode (DFM)
[0133] Scanning speed: 1.5Hz
[0134] Scanning range: 3μm×3μm
[0135] Resolution: 256 pixels x 256 pixels
[0136] For the obtained measured image, taking into account the curvature of the fiber cross section, the least square method is used by the attached software to find a primary plane from all the image data and fit it, and a primary tilt correction is performed to correct the tilt within the plane. Next, a secondary tilt correction is performed to correct the quadratic curve in the same way, and then the surface roughness analysis is performed by the attached software to calculate the surface area ratio relative to the assumed smooth surface. The measurement is performed by randomly sampling 5 different monofilaments, and each monofilament is measured once, for a total of 5 times, and the arithmetic average is used as the surface area ratio.
[0137] <Measurement of the adhesion ratio of the sizing agent applied to the carbon fiber bundle (Sz adhesion ratio)>
[0138] After weighing 2.0±0.5 g of the sample (W1) (read to the fourth decimal place), the sample was placed in an electric furnace (volume 120 cm 3 ) for 15 minutes to completely thermally decompose the sizing agent. Then, transfer to a container in a dry nitrogen flow of 20 liters / minute, cool for 15 minutes, weigh the carbon fiber bundle (W2) (read to the 4th decimal place), and calculate the sizing attachment amount from W1-W2. The sizing agent attachment amount is divided by W1 and converted to the value of mass % when the entire carbon fiber bundle containing the sizing agent is set to 100 mass % (rounding off the 3rd decimal place) as the attachment ratio (mass %) of the attached sizing agent. Perform 2 measurements, and use the average value as the attachment ratio (mass %) of the sizing agent.
[0139] <Measurement of epoxy value>
[0140] The epoxy value is obtained by immersing 30 g of the sample in 150 ml of N,N-dimethylformamide at a temperature of 25°C, performing ultrasonic treatment at a frequency of 40 kHz for 30 minutes each, and analyzing the sizing agent solution dissolved from the fiber. It should be noted that when the sizing agent is dissolved from the carbon fiber bundle to which the sizing agent is applied, it is preferred that the sizing agent remaining in the carbon fiber is less than 0.20% by mass. Using the dissolved sizing agent solution, the epoxy group is opened with hydrochloric acid, and the epoxy value is obtained by acid-base titration.
[0141] <Determination of overhang value>
[0142] like Figure 1As shown in FIG. 1 , a weight 3 with a load of 0.0375 [g / tex] was hung on a carbon fiber bundle 2 cut into 50 cm in an atmosphere at a temperature of 25°C and left for more than 30 minutes to eliminate the twisting habit. A portion 30 cm long from the center was sampled, as shown in FIG. Figure 2 As shown in the figure, the carbon fiber bundle is supported and placed so that it protrudes 25 cm from the rectangular horizontal platform 4 with an angle of 90° and the carbon fiber bundle 2 is not bent, and the carbon fiber bundle 2 on the horizontal platform 4 is fixed with tape. Then, the support of the protruding carbon fiber bundle 2 is removed from the horizontal platform 4, and it is hung down, and the length of the horizontal distance L from the support point is measured after 1 second. Five measurements are performed, and the arithmetic average thereof is taken as the drape value.
[0143] <Carbon fiber bundle process passability>
[0144] Two metal rods (stainless steel) with a diameter of 50 mm and a surface roughness Rmax of 0.3 μm were arranged in the vertical direction at an interval of 150 mm so that the carbon fiber bundle was in contact with and passed through each metal rod at an angle of 0.3925π (rad) ± 0.04π (rad), a total of 0.785π (rad). Then, a carbon fiber bundle with 12,000 filaments was laid on the metal rods, and the unwinding tension from the package was set to 800 g. The metal rods were pulled at 4 m / min by a driving roller, and the number of fluffs in 1 minute after passing through the second metal rod was counted as the process passing property.
[0145] Number of process fluffs of carbon fiber bundle (pieces / m) = the number of counted fluffs (pieces) / 4 (m)
[0146] A: The number of process fluff is less than 3.5 pieces / m
[0147] B: The number of process fluff is greater than 3.5 pieces / m and less than 5.0 pieces / m
[0148] C: The number of process hairs is greater than 5.0 pieces / m
[0149] It should be noted that, when the number of filaments in the measured carbon fiber bundle is 24,000, the above-mentioned unwinding tension is set to 1,600 g, and the number of process fluff counted is divided by √2, so that the process passability is calculated based on the same evaluation criteria. A and B are preferred results in the present invention, and A is a more preferred result.
[0150] <Pressure resistance of pressure vessels>
[0151] exist Figure 3The hydraulic pressure rupture test device for the pressure vessel shown in the figure is provided with a pressure vessel 11 as a sample, and water is supplied and pressurized by a hydraulic pump 7 to measure the rupture pressure when the vessel ruptures. The measurement is performed three times, and the pressure resistance is evaluated by the following judgment criteria for the arithmetic mean value thereof. It should be noted that "-" means that it was not measured.
[0152] A: Bursting pressure is above 75MPa
[0153] B: Bursting pressure is 70MPa or more and less than 75MPa
[0154] C: The bursting pressure is less than 70MPa.
[0155] [Preparation of sizing agent]
[0156] After ethylene oxide was added to bisphenol A by potassium hydroxide catalyst, the catalyst was treated to obtain ethylene oxide (2 mol) adduct of bisphenol A. 2 mol of the above ethylene oxide adduct of bisphenol A, 1.5 mol of maleic acid, and 0.5 mol of sebacic acid were added to a 1L flask equipped with a stirrer, a stirring blade, a nitrogen seal, and a distillation tower. While blowing nitrogen into the liquid, it was heated and stirred at 160°C for 4 hours, and the generated water was distilled off. 2 parts by mass of the condensate of the unsaturated dibasic acid and the alkylene oxide adduct of bisphenols obtained in this way, 2 parts by mass of "jER (registered trademark)" 828 (Mitsubishi Chemical Co., Ltd.), 1 part by mass of polyoxyethylene (70 mol) styrenated (5 mol) cumylphenol, and 95 parts by mass of distilled water were prepared to obtain a water-dispersible emulsion, thereby obtaining a sizing agent i. Next, the sizing agent i was heat-treated according to the conditions of Table 1 to obtain sizing agents ii and sizing agents iii.
[0157] [Table 1]
[0158]
[0159] In addition, a bisphenol A ethylene oxide 10 mol adduct represented by the following formula was used as a sizing agent iv.
[0160] [Chemical formula 1]
[0161]
[0162] [Example 1]
[0163] A copolymer obtained from acrylonitrile and itaconic acid was dissolved in dimethyl sulfoxide to prepare a spinning solution. The obtained spinning solution was temporarily extruded into the air from a spinning spinneret having 3,000 holes, and mixed with 80% by mass of dimethyl sulfoxide and 20% by mass of water as a coagulation accelerator (hereinafter, the mass ratio of components other than the coagulation accelerator in the coagulation bath liquid is also referred to as "coagulation bath concentration"), and introduced into a coagulation bath liquid controlled at -5°C to obtain coagulated fibers. The process of obtaining the coagulated fibers is simply referred to as "coagulation process".
[0164] In the water washing process, the coagulated filaments are introduced into a water washing bath and washed with water, and then in the stretching process, bath stretching is performed in warm water at 90°C. At this time, the total stretching ratio is set to 2.3 times. Next, in the oil agent imparting process, an amino-modified silicone-based silicone oil agent is imparted to the fiber bundle. Then, a drying treatment is performed using a heating roller at 180°C, and after the number of single fibers is set to 12,000, 5 times stretching is performed in pressurized steam, so that the total stretching ratio of the filament making is 12 times, and a polyacrylonitrile-based precursor fiber bundle with a single fiber fineness of 1.1 dtex is obtained.
[0165] Next, the obtained polyacrylonitrile-based precursor fiber bundle is processed in the following calcining step to prepare a carbon fiber bundle.
[0166] In the flame retardant treatment step, the obtained polyacrylonitrile-based precursor fiber bundle is subjected to flame retardant treatment in air at a temperature of 200 to 300° C. to obtain a flame retardant fiber bundle.
[0167] In the preliminary carbonization step, the flame resistant fiber bundle obtained in the flame resistant step is subjected to preliminary carbonization treatment in a nitrogen atmosphere at a maximum temperature of 800° C. to obtain a preliminary carbonized fiber bundle.
[0168] In the carbonization step, the pre-carbonized fiber bundle obtained in the pre-carbonization step is carbonized at a maximum temperature of 1,300° C. in a nitrogen atmosphere.
[0169] Next, electrolytic surface treatment was performed using a sulfuric acid aqueous solution as an electrolyte, and after washing and drying, a sizing agent i was applied to obtain a carbon fiber bundle.
[0170] Next, a mixture (mixture B) of "JER (registered trademark)" 828 / dicyandiamide / 3-(3,4-dichlorophenyl)-1,1-dimethylurea = 100 / 6.3 / 2 (parts by mass) was prepared.
[0171] Using a tow prep manufacturing device equipped with a warp creel, a kiss roll, a nip roll, and a winder, a mixture B adjusted to a temperature of 60°C is applied to one side of the obtained carbon fiber bundle in an amount of 22 to 28% by mass relative to the total mass of the tow prep, and then the mixture B is impregnated into the carbon fiber bundle through a nip roll to obtain a tow prep. At this time, for the winding bobbin of the tow prep, 2,300m is wound on a paper tube in a cylindrical manner with an initial tension of 600 to 1,000gf, a winding ratio of 6 to 10, and a winding width of 230 to 260mm. A 7.5L polyethylene liner is set on the filament winding molding device, and the tow prep is wound around the entire liner to produce a pressure vessel. Specifically, as the first layer, a ring layer at an angle of +89° relative to the axial direction of the liner and a ring layer at an angle of -89° relative to the axial direction of the liner are wound in such a manner that their thickness becomes 1.4mm. Next, as the second layer, a spiral layer at an angle of +20° to the axial direction of the liner and a spiral layer at an angle of -20° to the axial direction of the liner were wound in such a way that their thickness became 2.2 mm. Furthermore, as the third layer, an annular layer at an angle of +89° to the axial direction of the liner and an annular layer at an angle of -89° to the axial direction of the liner were wound in such a way that their thickness became 0.6 mm to obtain an intermediate. The intermediate was rotated in a curing furnace and cured at 130°C for 90 minutes to obtain a pressure vessel for a pressure test. The results are summarized in Tables 2 and 3.
[0172] [Example 2]
[0173] A carbon fiber bundle to which a sizing agent was applied was obtained in the same manner as in Example 1 except that the dimethyl sulfoxide content in the coagulation bath was 79 mass % (coagulation bath concentration 79 mass %).
[0174] [Comparative Example 1]
[0175] The temperature of the coagulation bath in the coagulation process was changed to 5°C, and the free roller in the coagulation process was changed to a fixed yarn guide to increase the friction resistance (coagulation yarn tension) to which the coagulated yarn was subjected. In addition, a carbon fiber bundle to which a sizing agent was applied was obtained in the same manner as in Example 1. Compared with Example 1, the coagulation yarn tension increased, the swelling degree of the coagulation yarn increased, and the density of the obtained precursor fiber bundle was insufficient. The bundle strength A' was 5.5 GPa, and the bundle strength B' was 4.5 GPa. Compared with Example 1, the bundle strength decreased significantly when using resin formulation B, and the strength utilization rate α was as low as 82%. The results are summarized in Tables 2 and 3. In addition, compared with Example 1, the pressure resistance of the obtained pressure vessel was also poor.
[0176] [Example 3]
[0177] A carbon fiber bundle to which a sizing agent was applied was obtained in the same manner as in Example 1, except that the number of holes in the spinning spinneret was 6,000 and the content of dimethyl sulfoxide in the coagulation bath was 82% by mass. At this time, the strand strength A' was 5.5 GPa, the strand strength B' was 4.9 GPa, and the strength utilization rate α was 89%. Compared with Comparative Example 1, in Example 3 in which the density of the precursor fiber bundle was good, the strand strength B' and the pressure resistance of the pressure vessel were improved. On the other hand, when focusing on the strand strength A', both Example 3 and Comparative Example 1 were 5.5 GPa, which was equivalent, and the result did not reflect the improved pressure resistance of the pressure vessel. The results are summarized in Tables 2 and 3.
[0178] [Example 4]
[0179] A carbon fiber bundle to which a sizing agent was applied was obtained in the same manner as in Example 1 except that the number of holes in the spinning spinneret was changed to 6,000. By increasing the number of holes in the spinning spinneret and reducing the frictional resistance borne by each coagulated filament, it was determined that the swelling degree was better than that in Example 1, indicating that a dense structure was obtained. At this time, the bundle strength A' was 5.7 GPa, the bundle strength B' was 5.0 GPa, and the strength utilization rate α was 88%. Compared with Example 1, the bundle strength was improved when the resin formulation B was used, and the strength utilization rate α was also increased. The results are summarized in Tables 2 and 3.
[0180] [Example 5]
[0181] The carbon fiber bundle to which the sizing agent was applied was obtained in the same manner as in Example 4 except that the adhesion ratio of the sizing agent was changed so that the interface shear strength became 14 MPa. At this time, the strand strength A' was 5.7 GPa, the strand strength B' was 5.2 GPa, and the strength utilization rate was 91%. In addition, the pressure resistance of the pressure vessel was improved compared with Example 1 and Comparative Example 1. The results are summarized in Tables 2 and 3.
[0182] [Comparative Example 2]
[0183] The fiber path in the coagulation process was changed so that the semi-solidified coagulated fiber bundle obtained by pulling the fiber bundle so that the immersion time in the coagulation bath was 0.2 seconds was retained in the air for 200 seconds to improve the density, and then the fiber bundle was subjected to the steps after water washing. In this case, a carbon fiber bundle to which a sizing agent was applied was obtained in the same manner as in Comparative Example 1. At this time, the swelling degree of the coagulated fiber was improved compared with Comparative Example 1, and the bundle strength A' was improved to 5.6 GPa and the bundle strength B' was improved to 4.7 GPa, but the strength utilization rate α was 84%, which was insufficient for use as a carbon fiber reinforced composite material. The results are summarized in Tables 2 and 3.
[0184] [Comparative Example 3]
[0185] A carbon fiber bundle to which a sizing agent was applied was obtained in the same manner as in Comparative Example 2 except that the number of holes in the spinning spinneret was changed to 6,000. In order to reduce the immersion time in the coagulation step, a fiber path for pulling the coagulated fiber bundle into the air is formed near the liquid surface where the spinning solution discharged from the spinneret is introduced into the coagulation bath. Therefore, as the number of holes in the spinneret is increased, the liquid surface of the coagulation bath is wavy, and the coagulated fibers are fused to each other, resulting in failure to obtain a precursor fiber bundle stably. The results are summarized in Tables 2 and 3.
[0186] [Table 2]
[0187] Table 2
[0188]
[0189] [Table 3]
[0190]
[0191] [Preparation of carbon fiber bundle before applying sizing agent]
[0192] The copolymer obtained from acrylonitrile and itaconic acid is dissolved in dimethyl sulfoxide as a spinning solution. The obtained spinning solution is temporarily extruded into the air from a spinning spinneret having the number of holes shown in Table 3, and a coagulated fiber bundle is obtained by a dry-wet spinning method in a coagulation bath obtained from an aqueous solution of dimethyl sulfoxide controlled at a temperature and concentration shown in Table 3. The fiber bundle is washed and stretched at 30 to 98°C by a conventional method. Next, an amino-modified silicone-based silicone oil agent is applied to the fiber bundle stretched in a water bath, and a drying and densification treatment is performed using a heating roller at 160°C. After the number of filaments reaches 12,000, it is stretched 5 times in pressurized steam, so that the total stretching ratio of the spinning is 12 times, and a polyacrylonitrile-based precursor fiber bundle with a single fiber fineness of 1.1 dtex is obtained.
[0193] Next, the obtained polyacrylonitrile-based precursor fiber bundles were combined as necessary so as to have the number of filaments shown in Table 3, and then processed in the following flame retardant step, preliminary carbonization step, and calcination step to prepare carbon fiber bundles.
[0194] In the flame retardant treatment step, the obtained polyacrylonitrile-based precursor fiber bundle is subjected to flame retardant treatment in air at a temperature of 200 to 300° C. to obtain a flame retardant fiber bundle.
[0195] In the preliminary carbonization step, the flame resistant fiber bundle obtained in the flame resistant step is subjected to preliminary carbonization treatment in a nitrogen atmosphere at a maximum temperature of 800° C. to obtain a preliminary carbonized fiber bundle.
[0196] In the carbonization step, the pre-carbonized fiber bundle obtained in the pre-carbonization step is carbonized at a maximum temperature of 1,300° C. in a nitrogen atmosphere.
[0197] Next, electrolytic surface treatment was performed using a sulfuric acid aqueous solution as an electrolyte, followed by water washing and drying to obtain a carbon fiber bundle I, a carbon fiber bundle II, a carbon fiber bundle III, and a carbon fiber bundle IV. The details are shown in Table 4.
[0198] [Table 4]
[0199]
[0200] [Examples 6 to 15, Comparative Examples 4 and 5, Reference Examples 1 to 25]
[0201] Sizing agent i, sizing agent ii, sizing agent iii or sizing agent iv was applied to carbon fiber bundle I, carbon fiber bundle II, carbon fiber bundle III or carbon fiber bundle IV as shown in Table 5. Then, heat treatment was performed at a temperature of 210° C. for 75 seconds to obtain a carbon fiber bundle to which a sizing agent was applied (however, no sizing agent was applied in Reference Example 1).
[0202] Next, a mixture (mixture C) of "Araldite (registered trademark)" LY1564 SP CI / "Baxxodur (registered trademark)" EC331 = 100 / 35 (parts by mass) was prepared.
[0203] A 7.5L polyethylene liner is set on a filament winding molding device, and the mixture C pre-mixed uniformly at 25°C is impregnated into the filament bundle of the carbon fiber bundle to which the sizing agent is applied in an amount of 22 to 28% by mass relative to the total mass of the carbon fiber bundle and the mixture C, and the filament is fed. As the first layer, the annular layer at an angle of +89° relative to the axial direction of the liner and the annular layer at an angle of -89° relative to the axial direction of the liner are wound in a manner that their thickness becomes 1.4mm. Next, as the second layer, the helical layer at an angle of +20° relative to the axial direction of the liner and the helical layer at an angle of -20° relative to the axial direction of the liner are wound in a manner that their thickness becomes 2.2mm. Further, as the third layer, the annular layer at an angle of +89° relative to the axial direction of the liner and the annular layer at an angle of -89° relative to the axial direction of the liner are wound in a manner that their thickness becomes 0.6mm to obtain an intermediate. After winding the carbon fiber bundle, the aforementioned intermediate is rotated at a speed of 7rpm and kept at 20°C for 15 minutes. The intermediate product was heated at 80° C. for 120 minutes and then at 110° C. for 240 minutes to solidify the mixture C, thereby obtaining a pressure vessel for a pressure test.
[0204] The details are summarized in Table 5. It should be noted that for Reference Example 1 to which no sizing agent is applied, Examples 11, 15, and Reference Examples 17 and 25 using a sizing agent iv that does not contain an epoxy group, the epoxy value is not measured. For Reference Example 1 to which no sizing agent is applied, due to the fuzzing and alignment disorder when measuring the bundle strength, the bundle strength A' is 5.1 GPa, which is low strength compared to the level of the carbon fiber bundle I to which the sizing agent is applied. In Reference Examples 2, 5, and 8 in which the interface shear strength is controlled by reducing the adhesion ratio of the sizing agent from Reference Example 11, it is confirmed that the bundle strength C' is improved, and in Reference Example 8, it is also confirmed that the pressure resistance of the pressure vessel is improved compared to Reference Example 11. In particular, in Reference Example 8 that satisfies Formula 1, an improvement in process passability is also confirmed compared to Reference Example 11. In Reference Examples 12 and 13, in which the interface shear strength was controlled by reducing the epoxy value of the sizing agent used in Reference Example 11, it was confirmed that the strand strength C' was improved, and in Reference Example 13, it was also confirmed that the pressure resistance of the pressure vessel was improved compared with Reference Example 11. In addition, in Reference Examples 12 and 13 that satisfied Formula 1, it was confirmed that the process passability was improved compared with Reference Example 11.
[0205] Compared with carbon fiber bundles I and III, in carbon fiber bundles II and IV, the spinning conditions are changed so that the swelling degree of the coagulated fibers when spinning the carbon fiber precursor fiber bundle is within a more preferred range. Compared with reference examples 1 to 17 using carbon fiber bundle I, in examples 6 to 11 using carbon fiber bundle II, the strand strength C' is improved. For example, compared with reference example 8, Example 7 uses sizing agent i and the adhesion ratio of the sizing agent is the same, but both the strand strength C' and the pressure resistance of the pressure vessel are confirmed to be improved. In addition, in Examples 7, 10, and 11 in which the adhesion ratio of the sizing agent or the epoxy value is further changed from Example 9 using carbon fiber bundle II in which the swelling degree of the coagulated fibers is within a preferred range to control the interface shear strength, both the strand strength C' and the pressure resistance of the pressure vessel are improved, and both the swelling degree of the coagulated fibers and the interface shear strength are appropriately controlled, thereby obtaining a carbon fiber bundle that is particularly preferred for use as a pressure vessel. When comparing Comparative Example 4 with Examples 7, 9, 10, and 11, the wire bundle strength A' of Comparative Example 4 is 5.7 GPa, which is equal to or higher than that of Examples 7, 9, 10, and 11. However, since the Sz agent adhesion ratio is large, Formula 1 is not satisfied, and since the interface shear strength is high, the wire bundle strength B' or the wire bundle strength C' is low, resulting in a low pressure resistance as a pressure vessel. Therefore, it is believed that the wire bundle strength A' does not necessarily reflect the pressure resistance of the pressure vessel, and it is important to improve the pressure resistance of the pressure vessel by appropriately controlling one or both of the coagulation filament swelling degree and the interface shear strength to improve the wire bundle strength B' or the wire bundle strength C'.
[0206] [Table 5]
[0207]
[0208] [Examples 16-17, Reference Examples 26-27]
[0209] The carbon fiber bundles of Example 9, Comparative Example 5, Reference Example 11, and Reference Example 22 were stored for 200 hours in a constant temperature and humidity environment at 60°C and a relative humidity of 90% for aging treatment, thereby obtaining carbon fiber bundles of Examples 16, 17, Reference Examples 26, and 27 corresponding to each Example, Comparative Example, or Reference Example. Then, a pressure vessel for pressure resistance test was obtained by the same method as that of the corresponding Example 9, Comparative Example 5, Reference Example 11, or Reference Example 22. The details are summarized in Table 6. No change was observed in the wire bundle strength A' before and after the aging treatment. On the other hand, the epoxy value decreased due to the aging treatment, so that Examples 16, 17, Reference Examples 26, and 27 satisfied Formula 1, and it was confirmed that the wire bundle strength C' was improved compared to before the aging treatment. In addition, the pressure resistance of the pressure vessel was improved by comparing Example 9 with Example 16 or Reference Examples 11 with 26.
[0210] [Table 6]
[0211]
[0212] For the carbon fiber bundles of Examples 1, 3, 5, 7, 9, 10, 11, 16, Comparative Examples 1, 4, Reference Examples 8, 11, 13, 17, and 26, the following resin formulation D was used and the strand strength (strength of strand D') was evaluated based on JIS R7608 (2007). It should be noted that the resin formulation D was heated to 60°C during impregnation. The details are shown in Table 7. Resin formulation D is a practical resin for strand prepregs, similar to resin formulation B. As in the case of using resin composition B or resin composition C, when using resin composition D, the carbon fiber bundle of the present invention exhibits a higher strand strength D' than the carbon fiber bundle of the comparative example. In addition, it was confirmed that the higher the strand strength D', the better the pressure resistance of the pressure vessel produced using resin composition B or resin composition C in each of the Examples, Comparative Examples, and Reference Examples.
[0213] Resin formulation D: "jER (registered trademark)" 828 / N,N-diglycidylaniline / dicyandiamide / 3-(3,4-dichlorophenyl)-1,1-dimethylurea = 60 / 40 / 7.6 / 2 (parts by mass) was used, and the curing conditions were normal pressure, temperature 130° C., and time 90 minutes.
[0214] [Table 7]
[0215] Table 7
[0216]
[0217] Description of Reference Numerals
[0218] 1: Fixed rod
[0219] 2: Carbon fiber bundle
[0220] 3: Weights
[0221] 4: Water platform
[0222] 5: Factory compressed air pipeline
[0223] 6: Booster
[0224] 7: Water pressure pump
[0225] 8: Liquid delivery hose
[0226] 9: Fixed mechanism
[0227] 10: Safety cover
[0228] 11: Pressure Vessel
[0229] 12: Data recording device
Claims
1. A carbon fiber bundle, which is a carbon fiber bundle to which a sizing agent is applied, wherein: The following resin formula A is used and the bundle strength (bundle strength A') evaluated based on JIS R7608 (2007) is 5.0 GPa or more and 6.0 GPa or less, the following resin formula B is used and the bundle strength (bundle strength B') evaluated based on JIS R7608 (2007) is 4.7 GPa or more and 5.5 GPa or less, the ratio of the bundle strength B' to the bundle strength A' is 85% or more, the single fiber diameter of the carbon fiber bundle is 6.0 μm or more, Resin formula A: "CELLOXIDE (registered trademark)" 2021P / boron trifluoride monoethylamine / acetone = 100 / 3 / 4 (parts by mass), and as curing conditions, normal pressure, temperature 125°C, and time 30 minutes; Resin formulation B: "JER (registered trademark)" 828 / dicyandiamide / 3-(3,4-dichlorophenyl)-1,1-dimethylurea = 100 / 6.3 / 2 (parts by mass), and curing conditions were normal pressure, temperature of 130° C., and time of 90 minutes.
2. The carbon fiber bundle according to claim 1, wherein The product E×d / W of the ratio d / W of the single fiber diameter d to the coil width W immediately before breakage evaluated by the single fiber coil method and the strand elastic modulus E is 12.6 GPa or more.
3. The carbon fiber bundle according to claim 1 or 2, wherein: The surface area ratio of a single fiber is 1.00 to 1.
08.
4. The carbon fiber bundle according to claim 1 or 2, wherein: The following resin formulation C is used and the strand strength (strength C') evaluated based on JIS R7608 (2007) is 4.8 GPa or more and 5.5 GPa or less, the ratio of the strand strength C' to the strand strength A' is 85% or more, the single fiber diameter of the carbon fiber bundle is 6.6 μm or more, and the interface shear strength is 16 MPa or less, Resin Formulation C: Araldite (registered trademark) LY1564 SP CI / Baxxodur (registered trademark) EC331 = 100 / 35 (parts by mass), and curing conditions were normal pressure, temperature 80° C., time 120 minutes, and then normal pressure, temperature 110° C., time 240 minutes.
5. The carbon fiber bundle according to claim 4, wherein: The beam strength C' is greater than or equal to 5.0 GPa and less than or equal to 5.5 GPa.
6. The carbon fiber bundle according to claim 4, wherein: The sizing agent contains at least one epoxy group-containing component, and the epoxy value of the sizing agent dissolved by immersing the carbon fiber bundle in N,N-dimethylformamide and performing ultrasonic treatment is Xmeq. / g, and the adhesion ratio of the sizing agent applied to the carbon fiber bundle is Y mass %, the following relationship is satisfied: 0.10meq. / g≤X×Y≤0.68meq. / g…Formula 1.
7. The carbon fiber bundle according to claim 4, wherein the drape value thereof is greater than 0 cm and is less than or equal to 18 cm.
8. The carbon fiber bundle according to claim 7, wherein the drape value is not less than 4 cm and not more than 10 cm.
9. A carbon fiber reinforced composite material using the carbon fiber bundle according to claim 1 or 2.
10. A pressure vessel using the carbon fiber bundle according to claim 1 or 2.
Citation Information
Patent Citations
Manufacture of bar code card
JP1985051987A
Production of ultrahigh strength carbon fiber
JP1992009227B2
Production of carbon fiber for producing superhigh-strength composite material
JP1993004463B2
Thermosetting resin composition and prepreg
JP2001323046A
Carbon fiber bundle for filament winding
JP2002294568A